The Benefits of Using Active Remote Patient Management for Enhanced Heart Failure Outcomes in Rural Cardiology Practice: Single-Site Retrospective Cohort Study - William Craig; Suzanne Ohlmann (JMIR Publications, 2024)
BackgroundRural populations have a disproportionate burden of heart failure (HF) morbidity and mortality, associated with socioeconomic and racial inequities. Multiple randomized controlled trials of remote patient monitoring (RPM) using both direct patient contact and device-based monitoring have been conducted to assess improvement in HF outcomes, with mixed results. ObjectiveWe aimed to assess whether a novel digital health care platform designed to proactively assess and manage patients with HF improved patient outcomes by preventing HF re-exacerbations, thus reducing emergency room visits and HF hospitalizations. MethodsThis was a single-site, retrospective cohort study using electronic medical record (EMR) data gathered from 2 years prior to RPM initiation and 2 years afterward. In January 2017, this single center began enrolling New York Heart Association (NYHA) class II and class III patients with HF prone to HF exacerbation into an RPM program using the Cordella HF system. By July 2022, 93 total patients had been enrolled in RPM. Of these patients, 87% lived in rural areas. This retrospective review included 40 of the 93 patients enrolled in RPM. These 40 were selected because they had 2 years of established EMR data prior to initiation of RPM and 2 years of post-RPM data; each consented to this Sterling IRB-approved study. ResultsWe included 40 patients with at least 4 years of follow-up, including 2 years prior to RPM initiation and 2 years after RPM initiation. In the 2 years after RPM initiation, check-up calls increased 519%, medication change calls increased 519%, and total calls increased by 519%. Emergency room visits for HF fell 93%, heart failure hospitalizations fell 83%, and all other cardiovascular hospitalizations fell 50%. Additionally, the total number of office visits declined by 15% after RPM, and unscheduled or urgent office visits declined by 73%. ConclusionsDaily monitoring of trends in vital sign data between engaged patients and a collaborative team of clinicians, incorporated into daily clinical workflow, enhanced patient interactions and allowed timely response or intervention when HF decompensation occurred, resulting in a reduction of outpatient and inpatient clinical use over more than 2 years of follow-up.